Dimensional predictors of response to SRI pharmacotherapy in obsessive–compulsive disorder - Landeros-Weisenberger, Angeli (2009)
BACKGROUND: Obsessive–compulsive disorder (OCD) is clinically heterogeneous. Previous studies have reported different patterns of treatment response to serotonin reuptake inhibitors (SRI) based on symptom dimension. Our objective was to replicate these results in OCD patients who participated in one of four randomized, placebo-controlled, clinical trials (RCT). METHODS: A total of 165 adult OCD subjects participated in one or more eight-week RCT with clomipramine, fluvoxamine, or fluoxetine. All subjects were classified as having major or minor symptoms in four specific OC symptom dimensions that were derived in a previous factor analytic study involving many of these same patients. Ordinal logistic regression was used to test the association between OC symptom dimensions and SRI response. RESULTS: We found a significant association between the symptom dimension involving sexual, religious and harm-related obsessions as well as checking compulsions (AGG/SR) and improved SRI response. This increased rate of SRI response was experienced primarily by individuals with harm-related obsessions. Over 60% of patients with AGG/SR OCD symptoms were rated as very much improved after SRI treatment. LIMITATIONS: As some of the RCTs included were conducted prior to the development of the Yale-Brown Obsessive–compulsive Scale (Y–BOCS), improvement in OCD severity was assessed using the Clinical Global Improvement (CGI) Scale. Data from the double-blind and open-label continuation phases of these trials was collapsed together to increase statistical power. CONCLUSIONS: Patients with OCD vary in their response to SRIs. The presence of AGG/SR symptoms is associated with an initial positive response to SRIs. These data add to the growing body of work linking central serotonin systems with aggressive behavior.